Determinants of Work Performance of Teachers in the Special Program in the Arts (SPA) in Region - Lady Ann S. Sabit; Fernando T. Herrera (Randwick International of Education and Linguistics Science Journal, 2024)
This study examines the determinants of work performance among Special Program in the Arts (SPA) teachers in Region X, Philippines, specifically within the divisions of Gingoog City, Misamis Oriental, and Cagayan de Oro. Employing a sequential explanatory mixed-method approach, the research initially gathered and analyzed quantitative data from SPA specialists and coordinators across Northern Mindanao. Participants completed self-rating questionnaires assessing their work performance and the manifestation of relevant performance factors. Subsequently, qualitative data were collected through interviews and focus group discussions with selected SPA teachers and students, aimed at providing deeper insights and contextual understanding of the quantitative findings. The thematic analysis identified recurring themes and patterns, informing the study's conclusions. Results indicated that the work performance of SPA specialists was generally rated from 'moderate' to 'fair,' with Dance and Media Arts receiving the highest ratings, though still within the moderate range. Professional development emerged as the primary predictor of work performance across most specializations. The study underscores the necessity of targeted professional development programs and recommends enhancements in administrative support, resource allocation, and policy advocacy to improve SPA implementation. These findings have significant implications for educational policy and practice in arts education.